Midterm Comparison of Tibial Fixation between Posterior Cruciate-Retaining and Substituting Porous Tantalum Total Knee Arthroplasty: Three-Dimensional Computed Tomography Analysis - Kaneko, Takao; Kono, Norihiko; Mochizuki, Yuta; Hada, Masaru; Toyoda, Shinya; Ikegami, Hiroyasu; Musha, Yoshiro (The Journal of Knee Surgery, 2019)
Porous tantalum tibial component is durable with excellent bone ingrowth, higher knee scores, and long-term survivorship. However, to our knowledge, the effect of posterior cruciate-retaining (CR) and posterior cruciate-substituting (PS) porous tantalum tibial component has not been reported. The aim of the current study was to investigate the prosthetic bone quality between CR porous tantalum tibial component and PS using three-dimensional multi-detector-row computed tomography (3D-MDCT). Porous twenty-two (22) CR total knee arthroplasties and 22 PS received 3D-MDCT at every 6 months up to 5.5 years postoperatively to assess prosthetic bone quality (bone marrow contents/tissue volumes [BMC/TV, mg/cm3]) underneath the pegs of porous tantalum modular tibial component. Clinical outcomes (Knee Society score [KSS], Western Ontario and McMaster Universities (WOMAC), FJS-12, Patella score) were evaluated at a minimum follow-up period of 5.5 years. No statistically significant differences were found in age, gender, body mass index, KSS, and BMC/TV volumes in the proximal tibia between the two groups before total knee arthroplasty (TKA). There were also no significant differences between the CR and PS groups with regard to BMC/TV at every 6 months up to 5.5 years after TKA. At 5.5 years postoperatively, there was no significant difference between the two groups in terms of the KSS, WOMAC, forgotten joint score (FJS-12), and Patella score. The present study revealed that the prosthetic bone quality of the CR porous tantalum tibial component and PS were equivalent at every 6 months up to 5.5 years after TKA. This study reflects level II evidence.
Keywords: posterior cruciate-retaining; posterior cruciate-substituting; porous tantalum tibial component; total knee arthroplasty; prosthetic bone quality